Formulation and evaluation of captopril loaded polymethacrylate and hydroxypropyl methycellulose microcapsules - Khamanga, Sandile Maswazi Malungelo (Rhodes University, Faculty of Pharmacy, Pharmacy, 2010)
Angiotensin-converting enzyme (ACE) inhibitors are some of the most commonly prescribed medications for hypertension. They are cited in many papers as the treatment most often recommended by guidelines and favoured over other antihypertensive drugs as first-line agents especially when other high-risk conditions are present, such as diabetic nephropathy. The development of captopril (CPT) was amongst the earliest successes of the revolutionary concept of structure-based drug design. Due to its relatively poor pharmacokinetic profile or short half-life of about 1 hour, the formulation of sustained-release microcapsule dosage form is useful to improve patient compliance and to achieve predictable and optimized therapeutic plasma concentrations. Currently, CPT is mainly administered in tablet form. One of the difficulties of CPT formulation has been reported to be its instability in aqueous solutions. CPT is characterized by a lack of a strong chromophore and, therefore, not able to absorb at the more useful UV"“Vis region of the spectrum. For this reason, an accurate, simple, reproducible, and sensitive HPLC-ECD method was developed and validated for the determination of CPT in dosage forms. The method was successfully applied for the determination of CPT in commercial and developed formulations. Possible drug-excipient and excipient-excipient interactions were investigated prior to formulating CPT microcapsules because successful formulation of a stable and effective solid dosage form depends on careful selection of excipients. Nuclear magnetic resonance spectroscopy, Fourier transform infra-red spectroscopy (FT-IR), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were used for the identification and purity testing of CPT and excipients. The studies revealed no thermal changes during stress testing of binary and whole mixtures which indicate absence of solid state interactions. There were no shifts, appearance and disappearance in the endothermic or exothermic peaks and on the change of other associated enthalpy values on thermal curves obtained with DSC method. Characteristic peaks for common functional groups in the FT-IR were present in all the mixtures indicating the absence of incompatibility. The techniques used in this study can be said to have been efficient in the characterization and evaluation of the drug and excipients. The technique of microencapsulation by oil-in-oil was used to prepare CPT microcapsules. The effects of polymer molecular weight, homogenizing speed on the particle size, flow properties, morphology, surface properties and release characteristics of the prepared CPT microcapsules were examined. In order to decrease the complexity of the analysis and reduce cost response surface methodology using best polynomial equations was successfully used to quantify the effect of the formulation variables and develop an optimized formulation thereby minimizing the number of experimental trials. There was a burst effect during the first stage of dissolution. Scanning electron microscopy (SEM) results indicated that the initial burst effect observed in drug release could be attributed to dissolution of CPT crystals present at the surface or embedded in the superficial layer of the matrix. During the preparation of microcapsules, the drug might have been trapped near the surface of the microcapsules and or might have diffused quickly through the porous surface. The release kinetics of CPT from most formulations followed Fickian diffusion mechanism. SEM photographs showed that diffusion took place through pores at the surface of the microcapsules. The Kopcha model diffusion and erosion terms showed predominance of diffusion relative to swelling or erosion throughout the entire test period. Drug release mechanism was also confirmed by Makoid-Banakar and Korsmeyer-Peppas models exponents which further support diffusion release mechanism in most formulations. The models postulate that the total of drug release is a summation of a couple of mechanisms; burst release, relaxation induced controlled-release and diffusional release. Inspection of the 2D contour and 3D response surfaces allowed the determination of the geometrical nature of the surfaces and further providing results about the interaction of the different variables used in central composite design (CCD). The wide variation indicated that the factor combinations resulted in different drug release rates. Lagrange, canonical and mathematical modelling were used to determine the nature of the stationery point of the models. This represented the optimal variables or stationery points where there is interaction in the experimental space. It is difficult to understand the shape of a fitted response by mere inspection of the algebraic polynomial when there are many independent variables in the model. Canonical and Lagrange analyses facilitated the interpretation of the surface plots after a mathematical transformation of the original variables into new variables. In conclusion, these results suggest the potential application of EudragitÂ® / MethocelÂ® microcapsules as suitable sustained-release drug delivery system for CPT.
Keywords: Hypertension -- Treatment; Hypertension -- Chemotherapy; Angiotensin converting enzyme -- Inhibitors; Hypotensive agents -- Development; Pharmacokinetics